Efek Fraksi n-Heksana Kulit Hylocereus polyhizus Terhadap Kadar Malondialdehida Tikus Stres Oksidatif - Sari, Wirna Maya; Wahdaningsih, Sri; Untari, Eka Kartika (UI Scholars Hub, 2014)
Excessive free radical production will lead to oxidative stress. One of the indicators used to determine stress oxidative is malondialdehyde (MDA). Hylocereus polyhizus peel is potential used natural exogenous antioxidant. The aim of this research was to study the effect of n-hexane fraction of H.polyhizus peel on MDA level and to determine the dose that could reduce the MDA level. H.polyhizus peel was macerated with chloroform, fractionated with n-Hexane. Rats were divided into 7 groups : normal, negative, positive control vitamin E (18 mg/ kgbw), positive control quercetin (4 mg/200gbw), H.polyhizus peel extract group treated with dose I (10mg/ 200gbw), dose II (20 mg/200gbw) and dose III (40 mg/200gbw). Each group consist of 4 rats and induced to oxidative stress by 10 minute swimming each day and food restriction for 5 days. Measurement of MDA level are using Spectrophotometer UV-Vis in 532 nm. MDA levels were analyzed using One way Anova and LSD test. The data shown that MDA level at normal, negative, positive vitamin E, positive kuersetin, dose I, II, III group is 0.042; 0.051; 0.034; 0.042; 0.038; 0.039; 0.042 µg/ml. The n-Hexane fraction of red dragon fruit peel was a potent antioxidant because posessing the ability to lowering the MDA level on stress oxidative rats.